Handbook of Chemical Risk Assessment: Health Hazards to Humans,Plants, and Animals - Eisler, Ronald (CRC Press, 2009)
Written over a period of 17 years, the Handbook of Chemical Risk Assessment exhaustively examines and analyzes the world literature on chemicals entering the environment from human activities. The three volumes cover chemicals recommended by environmental specialists of the U.S. Fish and Wildlife Service and other resource managers. The choices were based on the real or potential impact of each contaminant and on the knowledge available about their mitigation.